Synanthropy of Calliphoridae (Diptera) from La Pintada, Antioquia-Colombia - MONTOYA-G., AUGUSTO LEÓN; SÁNCHEZ-R., JUAN DAVID; WOLFF-E., MARTA (Revista Colombiana de Entomología, 2009)
Calliphoridae are found in a variety of habitats, showing preference for human environments, a phenomenon known as synanthropy. The medical, ecological and sanitary importance of these flies resides in their feeding and development habits, which occur in excrement, garbage, decomposing organic matter and animal carcasses. In addition, they are mechanical vectors of pathogens and causal agents of myiasis. The objective of this study was to determine the synanthropic index (SI) of adult Calliphoridae in La Pintada-Antioquia, Colombia, through simultaneous monthly samplings in three environments (urban, rural, and forest) using van Someren Rydon traps baited with human excrement, decomposing chicken viscera, fish and onion. Four traps (one for each bait) were placed in each environment for 48 hours each month, making collections every 12 hours.Atotal of 2406 individuals was captured belonging to 10 species. Chysomya megacephala (SI = + 96.47) showed the strongest preference for dense human settlements. Cochliomyia macellaria (SI = + 78.1), Lucilia eximia (SI = + 74,94) and Chysomya albiceps (SI = + 59.12) had preferences for human settlements (eusynanthropic). Hemilucilia semidiaphana (SI = -50) showed a preference away from human settlements (asynanthropic). Cochliomyia hominivorax, Chloroprocta idioidea, Lucilia cuprina, Hemilucilia segmentaria and Paralucilia pseudolyrcea were collected in small numbers, and their SI could not be determined. The monthly abundance and the efficiency of the attractiveness to baits are discussed according to their medical and sanitary importance. Paralucilia pseudolyrcea is recorded for first time in Colombia. Synanthropic species could be involved in the transmission of pathogens in this locality.